Challenges Encountered by EFL Teachers in Teaching Productive and Receptive Skills at SMP 2 Mattirobulu Pinrang - Irma, Irma (IAIN Parepare, 2021)
English teachers as a foreign language is a challenging task, particulary when it is done places where English serves a very limited purpose. This study attempted to investigate English teaching challenges as well as the solution taken by the EFL teachers at SMPN 2 mattirobulu. The study captured the English teachers’ point of view in facing teaching chllebges in the classroom and the solution they implemented to solve them through interview. A number of challenges emerged, partly coming from students, partly from teachers, and partly from the school’s facility. Students are challenged by their lack of vocabulary mastery, low concentration, lack of discipline, boredom, and speaking problem. Meanwhile, teachers’ challenges are shortage of teachers’ limited mastery of teaching methods and lack of professional development. In addition, facilities issues including inadequate resources and facilities, and time constraint. The solutions to overcome these challenges were also suggested in this study. The teacher asked the students to memorize the vocabulary. Without sufficient vocabulary, people cannot communicate and express their feeling both in form of spoken and written effectively. On the other hand making use of available resources and facilities.